ANALISIS KADAR KARBOHIDRAT PADA BIJI TUMBUHAN PAKIS HAJI (Cycas rumphii Miq) - John Elton Ngarbingan (BIOPENDIX, 2016)
Background: Food is one of the basic needs needed by the body every day in certain amounts as a source of energy and nutrients. In the body, food substances containing carbon elements can be used as energy-forming materials, one of which is carbohydrates obtained from various food sources. Pakis haji (Cycas rumphii Miq) is one type of Pakis haji (Cycas) commonly found in the archipelago that grows on different substrates. In Maluku people know Pakis Haji with the title of "king fruit", and use the leaves as vegetables, and the seeds processed into food. Methods: Sampling in Karangguli Village, Aru Islands District and analysis of carbohydrate levels in Basic Chemistry Laboratory of Faculty of Natural Science, Pattimura University of Ambon. The sample in this research is 5 gram of Pakis haji seed plant with the variable of carbohydrate level on the seed of haji fern plant. Carbohydrate analysis was performed using spectrophotometric method. Result: The result obtained is carbohydrate content on haji fern seed growing on soil substrate with lime stone is 50.95% and growing on sand substrate is 44.92%. These results indicate that the seeds of Pakis haji can be used as a major source of carbohydrates. Conclusion: Based on the result of research and data analysis, it can be concluded that carbohydrate level on Pakis haji seed (Cycas rumphii Miq) growing on soil substrate with lime stone is 50.95% and growing on sand substrate is 44.92%.